Analisis Kepuasan Masyarakat Terhadap Pelayanan E-Ktp di Kantor Kecamatan Kembang Janggut Menggunakan Metode Servqual - Nur Syariffah; Ivan Haristyawan; Rizky Zakariyya Rasyad (Management of Information System Journal, 2026)
E-KTP service is a form of public service that must be able to meet public expectations. However, various obstacles remain, such as the lengthy service process, lack of officer responsiveness, and technical constraints that have the potential to reduce public satisfaction. This study aims to analyze the level of public satisfaction with E-KTP services at the Kembang Janggut District Office using the SERVQUAL method. The study used a quantitative approach involving 83 respondents selected using the Slovin formula. Data were obtained through distributing questionnaires based on five SERVQUAL dimensions, namely tangibles, reliability, responsiveness, assurance, and empathy, then analyzed using the calculation of the gap value between public perceptions and expectations. The results showed that all dimensions had a negative gap value, which means the quality of service has not fully met public expectations. The responsiveness dimension had the largest gap value of -0.22, making it a top priority in service improvement, while the empathy dimension had the smallest gap value of -0.13, indicating that the attitude and attention of officers have been rated the best by the public. This research provides a contribution in the form of identifying service dimensions that are priority for improvement so that it can be a basis for the Kembang Janggut District Office in developing strategies to improve the quality of E-KTP services and increase public satisfaction.